Relationship between Primigravid women's awareness, attitude, fear of childbirth, and mode of delivery preference - Parisa khosravi; Soheila pirdadeh beiranvand; Behrouz beiranvand; Zahra Bostani Khalesi (Elsevier, 2022)
Introduction: Fear of childbirth is the main factor, which has decreased the tendency toward selecting natural birth. The immoderate increase in the number of C-sections has increased maternal and neonatal morbidity and mortality. The present study investigates the relationship between awareness, attitude, fear of childbirth, and mode of delivery preference in Primigravid women referring to healthcare centers in Khorramabad, Iran. Method: In this descriptive-analytic study, 179 nulliparous pregnant women with the gestational age of> 2,0 weeks who visited selected healthcare centers in Khorramabad for routine pregnancy care in 2020 were selected in two stages and studied. The data were collected via the childbirth attitude questionnaire (CAQ), awareness, attitude, demographic characteristics, current pregnancy characteristics, midwifery history, and history of infertility treatment questionnaires. The data were analyzed via the Chi-squared test. Results: The participants had a mean gestational age of 33.73 ± 4.71 weeks. There was a significant different between the level of awareness, and mode of delivery preference (p = 0.005). The majority of the participants (57.5%) had a moderate level of awareness about the mode of delivery. There was a significant different between the level of, attitude, and mode of delivery preference (p = 0.001).) Most of the participants (71.5%) had a negative attitude towards the mode of delivery. There was also a significant different between fear of childbirth and mode of delivery preference (p < 0.001), and most of the participants (71.5%) showed fear of childbirth. Conclusion: According to the results of this study, the majority of participants had afraid of childbirth, moderate awareness of mode of delivery, and negative attitudes. So, the healthcare providers should pay special attention to the fear of childbirth and the relevant factors during pregnancy.